From the south: the others as part of us, critical thinking in the anthropologies - Montoya Rojas, Rodrigo (2018)
Following the path that the discipline of anthropology has traveled in Peru throughout the Twentieth Century in relationship to other social and political processes that the country and Latin America faced, the author reflects upon the burgeoning of a critical thought in the anthropologies of Latin America and how critical we are of the different social sciences and what these do or fail to do with regards to the problems presented by reality to the inhabitants of each of these countries.